Pengaruh Komunikasi, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Nusa Jaya Indofast - Kellin; Wasiman Wasiman (Komunitas Dosen Indonesia, 2023)
In the year 2022, Indonesia made the decision to welcome citizens of other countries into the country. Due to the city's extremely strategic position, Batam is recognized as being one of the places in Indonesia that attracts a significant number of visitors. This presents an outstanding possibility for the launch of new travel and tourism businesses. In the city of Batam, there is a business by the name of PT Nusa Jaya Indofast that is active in this sector of the economy. In Batam, PT Nusa Jaya Indofast is recognized as the tour and travel business with the longest history of operation. There is an issue inside the organization in which the performance of the company's workers is below what is considered to be ideal as a result of inadequate communication amongst fellow employees. The firm does not have meetings very often, which results in poor contact with higher-ups, and in order to motivate employees, the corporation offers only little rewards and bonuses. When it comes to being disciplined at work, people are often less disciplined than they should be. The sampling method that has been decided upon is the saturated sample method, which is a sampling method that employs the full existing population of 106 respondents. This method has been considered to be the most appropriate method. The findings of the data that was gathered will be analyzed using SPSS 25, and then the data will be summarized into tabular form in order to make it simple to comprehend and read